2022
DOI: 10.7759/cureus.21078
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of STK11/LKB1 in Non-small Cell Lung Cancer

Abstract: There are two major groups of lung cancer: non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC). NSCLCs can be further separated into three different categories: lung adenocarcinoma, squamous cell carcinoma, and large cell carcinoma. Pulmonary adenocarcinomas represent nearly half of all lung cancer cases and are known to be caused by smoking, certain occupational exposures, and specific genetic mutations. Scientists have noticed that most NSCLCs are driven by defects in the following genes: EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 60 publications
0
25
1
Order By: Relevance
“…This suggests that they may both independently play a role as predictors of a higher PD-L1 expression. In addition, studies have also found a correlation between STK11 wild-type and PD-L1 expression and that loss of function in STK11 may yield a more aggressive cancer 18 20 32. However, no significant association for STK11 mutations and PD-L1 expression was found in the current study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…This suggests that they may both independently play a role as predictors of a higher PD-L1 expression. In addition, studies have also found a correlation between STK11 wild-type and PD-L1 expression and that loss of function in STK11 may yield a more aggressive cancer 18 20 32. However, no significant association for STK11 mutations and PD-L1 expression was found in the current study.…”
Section: Discussioncontrasting
confidence: 78%
“…Approximately 30% of lung adenocarcinomas in Europe have a mutation in KRAS 13–15 and mutations in KRAS generally predict poor survival among patients with lung cancer 16 . KRAS mutations have been associated with smoking13 and they often co-occur with other oncogenic alterations, especially loss-of-function mutations in STK11 or TP53 17–20. Mutations in TP53 and KRAS have been associated with an increased expression of PD-L1 and TMB 21–26.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, STK11 (serine threonine kinase 11) was identified as a significant tumor suppressor gene (Sumbly and Landry, 2022). Clinical data show that a wide variety of tumors carry STK11/ LKB1 abnormalities (Sumbly and Landry, 2022).…”
Section: Stk11/lkb1mentioning
confidence: 99%
“…In the 1990s, STK11 (serine threonine kinase 11) was identified as a significant tumor suppressor gene (Sumbly and Landry, 2022). Clinical data show that a wide variety of tumors carry STK11/ LKB1 abnormalities (Sumbly and Landry, 2022). STK11 encodes liver kinase B1 (LKB1), a protein kinase important in maintaining cellular energy balance (Sumbly and Landry, 2022).…”
Section: Stk11/lkb1mentioning
confidence: 99%
“…Some co-mutations occur frequently with KRAS mutations. One of these mutations, the STK11 mutation has been reported to induce resistance of NSCLCs to treatment and stem-cell-like properties [ 50 ] and might be also a target of interest.…”
Section: Molecular Radioresistance Mechanismsmentioning
confidence: 99%